NILAI SOSIAL DALAM NOVEL TANAH PARA BANDIT KARYA TERE LIYE - Humairotul Faizah (SulukAksara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to analyze the social values ​​contained in the novel Tanah Para Bandit by Tere Liye. This research is a descriptive qualitative research using Zubaidi's social value theory which divides social values ​​into 3 categories which include (1) Values ​​of Love, (2) Values ​​of Responsibility, and (3) Values ​​of harmony in life. This research uses the literary sociology approach of Renne Wellek & Austin Werren, they divide the study of the sociology of literature into 3 categories, namely the sociology of authors, the sociology of literary works, the sociology of literature. The primary data source used is in the form of quotations contained in the novel Tanah Para Bandit by Tere Liye which contain social values ​​in the novel. Secondary data obtained in this research is in the form of books, journals, articles, which discuss social values ​​in novels. Meanwhile, the data collection technique used in this research is by reading the entire novel Tanah Para Bandit by Tere Liye, then marking sentences, phrases or quotations that contain social values ​​with codes, then finally analyzing them and making conclusions. The results of this research are the manifestation of social values ​​contained in the novel Tanah Para Bandit by Tere Liye. There are 60 data regarding social values ​​in the novel, consisting of 24 values ​​of love, 20 values ​​of responsibility, and values ​​of harmony in life as many as 16 data.